Analisis Program Hutan Kemasyarakatan (HKm) di Desa Dara Kunci Kabupaten Lombok Timur Provinsi NTB - Susanti AS, Mey; Purnaweni, Hartuti; Kismartini, Kismartini (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2018)
This study aims to analyze (1) the implementation of Community Forest Program (HKm) by Wana Lestari Group in Dara Kunci Village, East Lombok NTB; (2) the supporting and inhibiting factors of program implementation. The research method is descriptive qualitative with reference to suitability between the implementation process of HKm Program with Regional Regulation of Province of NTB Number 6, 2004 concerning Guideline of Community Forest Implementation. To analyze the supporting and inhibiting factors refers to the theory of Conformity Model David C. Korten. The reason to choose Dara Kunci Village is because of several considerations that is Dara Kunci Village is one of three locations of HKm area in Lombok Island of West Nusa Tenggara Province, but the area in Dara Desa Village is often hit by flood disaster during rainy season and drought during dry season. Data collection techniques with in-depth interviews, literature study and observation. The result of the research shows that there is inconsistency with Regional Regulation of Province of NTB Number 6, 2004, because (1) motivation of beneficiary community to manage HKm area; (2) There has been no program evaluation by the government; (3) Seeds that are imported are not seasonally appropriate; (4) The technical implementation unit is not supported by adequate financial resources; (5) Area of ​​HKm area and number of groups resulted in less maximal assistance; (6) Community empowerment programs that are not properly targeted; (7) Development of community potential is not optimal.